Studies on Mechanical Properties of Composite Materials Based on Thermo Modified Timber - Khasanshin Romelevich (University of Zagreb, Faculty of Forestry and Wood Technology, 2013)
The paper presents the studies of the possibility of using thermo modified wood during the production process of composite materials. According to the studies, the infl uence of high-temperature processing of raw wood, without access of air oxygen, shows the feasibility of using this type of processing in the production of woodcement composites to improve their performance properties. It is established that high-temperature pre-treatment significantly reduces the “cement poisons”, such as water-soluble sugars in wood, reduces water absorption and swelling pressure development and, consequently, creates a composite material resistant to use under conditions of high humidity. A mathematical model was formulated that allows the determination of the ultimate strength of wood-concrete composite made from thermo modified wood particles according to the treatment temperature of the wood chips and the mixture ratio.